The 1945 Constitution of The Republic of Indonesia and The Constituent Assembly (In The Study of The Composition of Islamic Political Parties In The 1955 and 2024 Elections) - Kusuma, Sandi; Giyono, Urip (Universitas Sumatera Utara, 2024)
The Republic of Indonesia is a country founded on Pancasila and the 1945 Constitution of the Republic of Indonesia as its constitutional foundation. Throughout its history, Indonesian Muslims have played a crucial role in shaping the nation's foundation, notably through the Constituent Assembly. According to Article 134 of the 1950 United States of Indonesia Law regarding the Amendments to the Provisional Constitution of the United States of Indonesia, the Constituent Assembly, together with the government, was tasked with promptly establishing a new Constitution to replace the Provisional Constitution. The Constituent Assembly was established during the Liberal Democracy period from 1950 to 1959, following the 1955 General Elections, which involved various political parties, groups, institutions, and individuals. The four major parties that garnered the most votes were the Indonesian National Party (PNI), the Indonesian Muslim League (Masyumi), Nahdlatul Ulama (NU), and the Indonesian Communist Party (PKI), representing three major ideological streams: Nationalist, Islamic, and Socialist-Communist. In this context, the author will analyze the composition of Islamic political parties in the 2024 General Elections to understand how the dynamics of Islamic parties and their representation might influence policy formulation and the direction of governance in contemporary Indonesia.